KOMPETENSI GURU DALAM PENYUSUNAN INSTRUMEN IPS DI SDIT AL- FITYAN KECAMATAN SOMBA OPU KABUPATEN GOWA - Mirnawati Mirnawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to describe teachers' ability to determine the supporting and inhibiting factors of teacher competence in the preparation of assessment instruments for social studies subjects. The type of research used is qualitative research through a descriptive approach, by determining the sample by purposive sampling consisting of the principal, teachers in grades III and VI, and students in grades III and VI. This study concluded that teachers who taught already had good pedagogical competencies in the preparation of assessment instruments. Also, increasing pedagogical competence is supported by supporting factors for teacher competence, namely: 1) High level of education. 2) Participation in various training and scientific activities. 3) The period of work and work experience. 4) Level of welfare. 5) Awareness of obligations and responsibilities. 6) Availability of facilities and infrastructure. 7) Principal leadership. 8) guidance activities undertaken. The inhibiting factor for teacher pedagogical competence is a lack of understanding of the 2013 curriculum assessment.